Regulating Electronic Notarial Deeds: A Jurisdictional Perspective from Indonesia - Syadzwina Hindun Nabila (Generate Digital Publishing, 2026)
Objective: To analyze the legal framework of electronic notarial deeds (cyber notary) from a jurisdictional perspective, examine their evidentiary value within the Indonesian legal system, and evaluate the level of harmonization between the Notary Profession Law (UUJN) and the legal regime governing electronic documents and transactions. Research Design & Methods: This study employs a normative legal research method using legislative, conceptual, and comparative approaches to assess the consistency and alignment of relevant legal frameworks, including the Civil Code, UUJN, and the ITE Law. Findings: The study identifies significant inconsistencies and regulatory gaps between the requirements for authentic deeds under the Civil Code and the recognition of electronic documents under the ITE Law. These discrepancies lead to legal uncertainty regarding notarial jurisdiction, the validity of electronic deeds and protocols, and the recognition of electronic signatures, particularly in cross-border transactions. Contributions: This study provides conceptual and normative contributions to the development of notarial law in the digital era by emphasizing jurisdiction as a central issue in cyber notary practices and proposing a framework for regulatory harmonization. Practically, it offers guidance for policymakers and legal practitioners in formulating clearer regulations and standardized electronic notary procedures. Academically, it enriches legal discourse on the intersection between conventional notarial principles and digital legal systems, while socially, it supports improved public access to legal services. Novelty: The novelty of this study lies in its focus on jurisdictional aspects as the core issue in cyber notary implementation, along with proposing the adaptation of the lex loci actus principle into the digital context and the development of a standardized electronic notary protocol.